Number of tooth loss in smokers and non-smokers in Monmata Lhoong Village, Aceh Besar District, Indonesia - Rahmayani, Liana; Saputri, Dewi; Chairunas, Chairunas; Syahrial, Syahrial; Maisura, Maisura (Universitas Padjadjaran, 2019)
Introduction: Tooth loss is a condition that occurs in most of the world's population. The most common causes of tooth loss are caries and periodontal disease. Periodontal disease can usually increase or getting worse by bad habits such as smoking. Smoking accelerates the course of periodontal disease and decreases salivary secretion, whereby increased the risk of caries incidence. Some components of the cigarette’s smoke that can accelerate the course of periodontal diseases are nicotine and tar. The purpose of this study was to determine the difference in the number of tooth loss in smokers and non-smokers. Methods: This study was a cross-sectional study. The sampling method was by the tables of Isaac and Michael, involving 78 smokers and 78 non-smokers in the village of Monmata Lhoong District. Results: Analysis was performed using the Mann-Whitney test. The result showed a significant difference between tooth loss in smokers and non-smokers (p < 0.05). Conclusion: The average value of tooth loss number in smokers is higher (96.47) than the non-smokers (60.53).Keywords: Tooth loss, cigarette, periodontal disease, nicotine, smoker, non-smoker